The Accuracy of a Non-invasive Liver Fibrosis Evaluation Method, Shear Wave Elastography : A Retrospective Pilot Study - Satoshi KOTANI; Shuichi SATO; Naruaki KOHGE; Kosuke TSUKANO; Sayaka OGAWA; Satoshi YAMANOUCHI; Ryusaku KUSUNOKI; Masahito AIMI; Yoichi MIYAOKA; Hirofumi FUJISHIRO; Tomohiko YAMAMOTO; Hideyuki OHNUMA (Shimane Journal of Medical Science, 2017)
Objective: We aimed to evaluate the diagnostic accuracy of shear wave elastography( SWE) for the assessment of liver fibrosis in patients with liver disease. Methods: A total of 54 consecutive patients who underwent SWE measurement and liver biopsy were included. Receiver-operator characteristic (ROC) curves were constructed to calculate the area under the ROC curve (AUC) for F0-2 versus F3-4 and F0-3 versus F4. Results: Fibrosis scores estimated by SWE were F0 for 9 cases, F1 for 18 cases, F2 for 11 cases, F3 for 9 cases, and F4 for 7 cases. AUCs for severe fibrosis (F3 and F4) and cirrhosis (F4) were 0.931 (P < 0.001) and 0.916 (P < 0.001), respectively. Shear wave velocity correlated significantly with liver fibrosis obtained by liver biopsy (r = 0.679, P < 0.001). Conclusion: SWE is a useful and non-invasive technology to estimate liver fibrosis in liver disease regardless of etiology.